P3.122 Significant decrease of CD4+ t-cells between recent and long-term infection in HIV-1 subtypes NON-B in the northeast brazil. (8th July 2017) - Lima, Kledoaldo Oliveira De; Leal, Élcio; Cavalcanti, Ana Maria Salustiano; Salustiano, Daniela Medeiros; Lacerda, Heloísa Ramos
Abstract : Introduction: Immunoassays for detection of HIV-1 recent infection are important in guiding prevention policies in more affected groups and, especially, in the monitoring of antiretroviral resistance when performed in conjunction with genotyping assays. The objective of this study was to evaluate the frequency of individuals with HIV-1 recent infection and to relate infection status to viral load, CD4+ T cells count and viral subtype. Methods: One hundred and one samples from individuals diagnosed with HIV-1 were obtained from five Voluntary and Counselling Testing Centres (VCTs) in the state of Pernambuco (Northeast - Brazil), from 2007 to 2009, and tested by BED-CEIA Enzyme Immunoassay for determination of recent/long-term infection. Then, the HIV-1 pol region was sequenced through TRUGENE HIV-1 Genotyping assay. Phylogenetic analyses were performed by the maximum likelihood method with MEGA software. Results: Among the 101 sequences analysed, 54 (53.5%) were HIV-1 subtype B and 47 (46.5%), non-B subtypes. The recent infection rate was 22.2% (n=12) and 19.1% (n=09) for subtypes B and non-B. In non-B subtypes there were a significant decrease in CD4+ T cells count between recent and long-term infections compared to subtype B (p=0.002). There was no statistical difference in viral load levels and infection status for the analysed subtypes. Conclusion: Decreases in CD4+ T cells count in the course of infection by non-B subtypes may indicate a propensity for disease progression by these variants. Thus, genotyping, antiretroviral resistance, and infection status assessments are important for monitoring local epidemics.